The boomerang effect of the cassava floor price policy: An analysis of the impact of the governor of Lampung’s directive on the tapioca industry and farmers’ welfare - Umayasari, Ulfa; Amantha, Goestyari Kurnia (Privietlab, 2025)
This study analyzes the impact of Governor of Lampung's Instruction No. 2 of 2025, which sets a floor purchasing price for cassava at IDR 1,350 per kilogram, with a maximum deduction (rafaksi) of 30% and without consideration of starch content. Although the policy aimed to protect farmers from plummeting prices, it triggered a complex chain reaction. Employing a case study approach and analyzing secondary data from news sources and relevant literature, this study finds that the policy directly led to the temporary shutdown of most tapioca factories in Lampung. While farmers initially welcomed the price benchmark, factory closures resulted in difficulties in absorbing harvested cassava and posed the risk of significant losses for farmers. The analysis revealed that the policy's disregard for quality factors, particularly starch content, and failure to consider the economic viability of the processing industry were key drivers of resistance from factory owners. Subsequent interventions by regional and national governments, including the proposal of a Limited Import Ban (Lartas) on tapioca and the involvement of the Food Task Force, along with negotiations involving business associations, eventually pressured many factories to resume operations and comply with new pricing. Nonetheless, this episode highlights the vulnerability of farmers, the complexity of price interventions in agricultural commodity markets, and the urgent need for a holistic policy approach. This study recommends a reformulation of floor price policies that incorporate quality-based incentives, promote equitable partnership models, strengthen farmers’ capacity, ensure better coordination between regional and central governments, and include well-calibrated import regulations.